THE CORELATION IN STRESS LEVELS AND BLOOD SUGAR LEVELS OF YOUNG PARENTS WITH DIABETES MELLITUS IN RT 007 RW 001 JAYALAKSANA VILLAGE CABANGBUNGIN DISTRICT, BEKASI REGENCY: HUBUNGAN TINGKAT STRESS DENGAN KADAR GULA DARAH ORANG TUA MUDA PENDERITA DIABETES MELLITUS DI RT 007 RW 001 DESA JAYALAKSANA KECAMATAN CABANGBUNGIN KABUPATEN BEKASI - Maswiyah Maswiyah; Nurti Yunika Kristina Gea; Ernauli Meliyana (Akademi Keperawatan Yarsi Samarinda, 2023)
Diabetes Mellitus (DM) is a disorder of the pancreas, an organ that can produce insulin. Diabetes cannot be cured, but it can be controlled with lifelong medication. People with diabetes mellitus of course have taboos on eating foods that contain a lot of sugar and reduce fat consumption because it is feared to make blood sugar exceed normal limits. Stress experienced by people with diabetes mellitus can have an impact on glucose control disorders. In a state of stress there will be an increase in excess production of cortisol, high stress can trigger an increase in blood glucose levels in the body, so that the higher the stress experienced by people with diabetes mellitus, the diabetes mellitus suffered also gets worse. Objective: To determine the relationship between stress levels and blood sugar levels of young parents with diabetes mellitus in RT 007 RW 001 Jayalaksana Village, Cabangbungin District, Bekasi Regency. Research method: This study used an analytic observational research design using a cross sectional approach. The population of this study was 101 respondents. To determine the number of samples in this study using the Slovin formula, the sample in this study was 81 respondents. The sampling technique in this study uses non-random (Non Probability) sampling (Purposive Sampling). research results: Based on the results of statistical analysis using the chi square test, the p value of 0.002 <0.05 was obtained. This shows that H0 is rejected. Conclusion: There is a relationship between stress levels and blood sugar levels of young parents with diabetes mellitus in RT 007 RW 001 Jayalaksana Village, Cabangbungin District, Bekasi Regency.